Développement agricole et gouvernance foncière à Tioroniaradougou (Nord de la Côte d’Ivoire) - Jérôme Aloko-N’guessan; Marthe Adjoba Koffi-Didia; Hamed Tiécoura Coulibaly (EchoGéo)
The Tioroniaradougou zone, like other Ivorian regions, is facing an evolution of traditional land governance. Although these transformations seem difficult to reconcile with customary requirements, they tend to become permanent because of agricultural development combined with demographic pressure. This study aims to understand the impact of agricultural development on the evolution of land governance strategies in Tioroniaradougou. The approach adopted is based on bibliographic research and fieldwork. The results show that the agricultural development of the soil is linked to the growth of cash crops such as cotton, cashew nuts and mangoes. With the diffusion of these crops, guaranteeing sure and regular income, farmers establish strategies of affirmation of their right of property ownership where customary land governance grants only a right of temporary use. The establishment of farmland by peasants is also a strategy to assert the rights of alienation on limited land resources.